Answer:
2.86310
Step-by-step explanation:
It is small but is larger than two
Answer:
![n=-2,\:n=-1](https://tex.z-dn.net/?f=n%3D-2%2C%5C%3An%3D-1)
Step-by-step explanation:
![\left(n+2\right)\left(n+1\right)=0\\\mathrm{Using\:the\:Zero\:Factor\:Principle:\quad \:If}\:ab=0\:\mathrm{then}\:a=0\:\mathrm{or}\:b=0\:\left(\mathrm{or\:both}\:a=0\:\mathrm{and}\:b=0\right)\\\mathrm{Solve\:}\:n+2=0:\quad n=-2\\n+2=0\\\mathrm{Subtract\:}2\mathrm{\:from\:both\:sides}\\n+2-2=0-2\\\mathrm{Simplify}\\n=-2\\\mathrm{Solve\:}\:n+1=0:\quad n=-1\\n+1=0\\\mathrm{Subtract\:}1\mathrm{\:from\:both\:sides}\\n+1-1=0-1\\Simplify\\n=-1\\](https://tex.z-dn.net/?f=%5Cleft%28n%2B2%5Cright%29%5Cleft%28n%2B1%5Cright%29%3D0%5C%5C%5Cmathrm%7BUsing%5C%3Athe%5C%3AZero%5C%3AFactor%5C%3APrinciple%3A%5Cquad%20%5C%3AIf%7D%5C%3Aab%3D0%5C%3A%5Cmathrm%7Bthen%7D%5C%3Aa%3D0%5C%3A%5Cmathrm%7Bor%7D%5C%3Ab%3D0%5C%3A%5Cleft%28%5Cmathrm%7Bor%5C%3Aboth%7D%5C%3Aa%3D0%5C%3A%5Cmathrm%7Band%7D%5C%3Ab%3D0%5Cright%29%5C%5C%5Cmathrm%7BSolve%5C%3A%7D%5C%3An%2B2%3D0%3A%5Cquad%20n%3D-2%5C%5Cn%2B2%3D0%5C%5C%5Cmathrm%7BSubtract%5C%3A%7D2%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D%5C%5Cn%2B2-2%3D0-2%5C%5C%5Cmathrm%7BSimplify%7D%5C%5Cn%3D-2%5C%5C%5Cmathrm%7BSolve%5C%3A%7D%5C%3An%2B1%3D0%3A%5Cquad%20n%3D-1%5C%5Cn%2B1%3D0%5C%5C%5Cmathrm%7BSubtract%5C%3A%7D1%5Cmathrm%7B%5C%3Afrom%5C%3Aboth%5C%3Asides%7D%5C%5Cn%2B1-1%3D0-1%5C%5CSimplify%5C%5Cn%3D-1%5C%5C)
![\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}\\n=-2,\:n=-1](https://tex.z-dn.net/?f=%5Cmathrm%7BThe%5C%3Asolutions%5C%3Ato%5C%3Athe%5C%3Aquadratic%5C%3Aequation%5C%3Aare%3A%7D%5C%5Cn%3D-2%2C%5C%3An%3D-1)
A, B, D, and E are correct.
What makes these a function and the others not is that for each x value, there is only one y value. For C, for example, there are multiple y values for the x value of -2. The same goes for F.
Answer:
10
Step-by-step explanation:
Seeing the 5 12 13 triple you get 1/2x=5 so
x=10
Answer:9/4
Step-by-step explanation:
3/4 + (1/3/1/6) - (1/2)
3/4 + (1/3 ➗ 1/6) - 1/2
3/4 + (1/3 x 6/1) - 1/2
3/4 + ((1x6)/(3x1)) - 1/2
3/4 + (6/3) - 1/2
3/4 + 2 - 1/2
(3+8-2)/4
9/4